Konsep Pembinaan Hizbut Tahrir dan Dampaknya Terhadap Akhlak Remaja - Lutfi, Muhamad; Sobari, Ahmad; Rofi'ah, Rofi'ah (Universitas Ibn Khaldun Bogor, 2021)
The concept of fostering Hizb ut-Tahrir and its impact on youth morals in the city of Bogor. This study discusses the concept of fostering Hizb ut-Tahrir and its impact on adolescent morals in the city of Bogor. The research objectives are (1) to find out the concept of coaching Hizb ut-Tahrir Indonesia for adolescents in the city of Bogor, (2) to find out the propaganda activities of Hizb ut-Tahrir Indonesia in adolescent moral development in the city of Bogor, (3) to find out the impact of the coaching conducted by Hizb ut-Tahrir Indonesia on the morals of adolescents in the city of Bogor. In this study using a qualitative approach with descriptive analysis method. In this study researchers used interview techniques in data collection. Interviews were conducted directly and in depth to and use snowball sampling. The results obtained that the concept of coaching carried out by the Hizb ut-Tahrir DPD in the City of Bogor towards adolescent moral development is tastqif hos and tastqif amm or general coaching and special coaching. Tastqif hos is a special coaching for the members and sympathizers of Hizb ut-Tahrir while tastqif amm is coaching for the general public and holding demonstrations to broadcast Islam to the public and to criticize non-Islamic policies. Hizb ut-Tahrir's activity is to carry out Islamic da'wah to change the condition of a damaged society into an Islamic society, by turning ideas into Islamic ideas, so that they will become public opinion in the community, and become a perception for them, which will encourage and implement it in accordance with the demands of Islam. Of the nine respondents who were the object of research, the authors found that the concept of coaching carried out by Hizb ut-Tahrir was very effective. Because the data from the nine respondents the researchers got, all the respondents felt a very positive impact when attending coaching on the Hizb ut-Tahrir.AbstrakKonsep Pembinaan Hizbut Tahrir Dan Dampaknya Terhadap Akhlak Remaja Di Kota Bogor. Penelitian ini membahas tentang Konsep Pembinaan Hizbut Tahrir Dan Dampaknya Terhadap Akhlak Remaja Di Kota Bogor. Tujuan penelitian ini adalah (1) Untuk mengetahui konsep pembinaan Hizbut Tahrir Indonesia bagi remaja di Kota Bogor, (2) Untuk mengetahui kegiatan dakwah Hizbut Tahrir Indonesia dalam pembinaan akhlak remaja di Kota Bogor, (3) Untuk mengetahui dampak dari pembinaan yang dilakukan Hizbut Tahrir Indonesia terhadap akhlak remaja di Kota Bogor. Dalam penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif analisis. Dalam penelitian ini peneliti menggunakan teknik wawancara dalam pengumpulan data. Wawancara dilakukan secara langsung dan mendalam untuk serta menggunakan snowball sampling. Hasil yang diperoleh bahwa konsep pembinaan yang dilakukan Hizbut Tahrir DPD Kota Bogor terhadap pembinaan akhlaq remaja adalah tastqif hos dan tastqif amm atau pembinaan umum dan pembinaan khusus. Tastqif hos merupakan pembinaan husus bagi para anggota dan simpatisan Hizbut Tahrir sedangkan tastqif amm adalah pembinaan yang dilakukan untuk masyarakat umum dan melakukan unjuk rasa untuk mensyiarkan Islam ke publik dan untuk mengkritisi kebijakan yang tidak Islami. Kegiatan Hizbut Tahrir adalah mengemban dakwah Islam untuk merubah kondisi masyarakat yang rusak menjadi masyarakat Islam, dengan merubah ideide menjadi ide-ide Islam, sehingga akan menjadi opini umum di tengah-tengah masyarakat, serta menjadi persepsi bagi mereka, yang akan mendorongnya untuk merealisir dan menerapkannya sesuai dengan tuntutan Islam. Dari sembilan responden yang menjadi objek peneltian, penulis menemukan bahwasannya konsep pembinaan yang dilakukan Hizbut Tahrir terbilang sangat efektif. Karena data dari sembilan responden yang peneliti dapatkan, semua responden merasakan dampak yang sangat positif ketika mengikuti pembinaan di Hizbut Tahrir.